Case report: Cerebral artery air embolism during CT-guided lung nodule resection in hybrid theater - Xing, Huajie; Wang, Zhiqiang; Jiang, Yuequan (Frontiers in Surgery, 2022)
A middle-aged male received CT-guided lung nodule localization and segmentectomy for a 10-mm lesion in the right upper lung. He developed left side paralysis after surgery, which was proved to be cerebral artery air embolism caused by a CT-guided lung puncture. He achieved almost full recovery with hyperbaric oxygen therapy and intensive rehabilitation. This case highlights the possibility of cerebral artery air embolism during CT-guided lung nodule resection in hybrid theater, with emphasis on prevention and early detection of this life-threatening complication.